The Relationship between Self-Efficacy and Self-Care Management in Hypertensive Patients with Comorbidities - Apriyani Yesika; Arina Maliya (Indonesian Journal of Global Health Research, 2025)
This study aims to examine the relationship between self-efficacy and self-care management in individuals with hypertension and comorbid diabetes mellitus at the Kartasura Health Center. This research uses a quantitative approach with a correlational design. The study population consists of individuals with hypertension and comorbid diabetes mellitus registered at the Kartasura Health Center, totaling approximately 470 people. A sample of 88 respondents was selected using purposive sampling. Data were collected through a questionnaire measuring self-efficacy and self-care management, which had been tested for validity and reliability (Cronbach’s Alpha > 0.60). The normality test showed a normal distribution with a significance value > 0.05 based on the Kolmogorov-Smirnov test. Data analysis was conducted using Pearson correlation tests with the help of SPSS software. The results indicate a significant correlation between self-efficacy and self-care management in individuals with hypertension and comorbid diabetes mellitus. Those with higher levels of self-efficacy tend to be more adherent to medication and better manage their health conditions, contributing to more stable blood pressure control. This study concludes that self-efficacy significantly influences self-care management in individuals with hypertension and comorbid diabetes mellitus.